Building a Shared ASEAN Identity: The ASEAN University Network (AUN) and its role in Advancing Regional Integration - Ahmad Syah Alfarisi (Dauliyah Journal of Islamic and International Affairs, 2026)
ASEAN has achieved remarkable success in uniting one of the most diverse regions in the world into a relatively stable, peaceful, and growing economic bloc. In 2015, ASEAN established the ASEAN Community under three pillars: the ASEAN Political-Security Community (APSC), the ASEAN Economic Community (AEC), and the ASEAN Socio-Cultural Community (ASCC). Within this framework, ASEAN aims to build a resilient, innovative, dynamic, and people-centered community, grounded in regional solidarity and cooperation. As part of the ASCC, the ASEAN University Network (AUN) represents one of ASEAN’s most prominent people-centered initiatives, promoting collaboration among universities, students, and academic staff across the region. This study argues that AUN contributes to the building of ASEAN identity by creating spaces for social interaction and shared experiences through educational cooperation, quality assurance mechanisms, and short-term mobility initiatives such as AUN Summer Camps, youth forums, and thematic network activities. These initiatives support people-to-people engagement and contribute to regional integration in Southeast Asia. However, the effectiveness and inclusiveness of AUN remains constrained by structural funding limitations within ASEAN itself, which in turn affects negatively in AUN’s institutional capacity. Without stronger political commitment and reforms in ASEAN’s funding mechanism, the long-term goal of fostering a deeply rooted ASEAN identity will remain difficult to achieve.